Stability of Charlie's method on linear heat conduction equation. - Osman, Halijah; Wood, A. S. (Department of Mathematics, Faculty of Science, 2001)
Explicit schemes are attractive for obtaining finite difference solutions to partial differential equations because of their simplicity. However this feature is undermined by the severe restriction on stability that the schemes suffer. One method that appears to have better stability properties is Charlie's method. The stability region of this method applied to a one-dimensional heat conduction equation is discussed in this article.